AB0545 An Audit of New Patient Referrals to A Dedicated Primary SjÖGren's Syndrome Clinic. (10th June 2014) - Batten, R.L.; Ng, W.-F.
Abstract : Objectives: The aim of this audit is to review new-patient referrals to a Primary Sjögren's Syndrome (PSS) clinic in the North East of England. We reviewed the referral pathway, timing from initial symptoms to referral, diagnosis and treatment, geographic distribution of referrals, whether these patients are being assessed appropriately and did they meet AECG criteria for a diagnosis of PSS. The aim is to inform service design, including education and raising awareness of the need for timely referral in these patients, setting up inter-specialty links with a view to possible combined clinics in the future, and developing a pro forma for initial assessment of these patients, with the ultimate goal to improve the standard of care for PSS sufferers Methods: A list of all new suspected PSS referrals between January 2009 and September 2013 was obtained from the hospital database. Notes, including clinic letters, blood tests, x-ray reports and referral letters were reviewed. Results: A Total of 169 patients were referred to the specialist clinic. Of these, 156 had been seen at least once. Of those who had not been seen, 5 patients did not attend their scheduled appointment (2.9%) and 8 had yet to receive a first appointment. Data was missing for 6 of the patients who attended the specialist clinic. Data for a total of 150 patients was analysed. The age at referral to specialist clinic ranged from 16 to 87, mean age 58.2 years. Male to female ratio 1:5. Time from initial symptoms to referral to specialist Sjögren's clinic ranged from 2 months to 252 (mean 77.2) months. Time from first presentation to a medical specialty to attendance at the specialist PSS clinic ranged from 0 to 240 (mean 41.2) months. Patients were referred from a variety of pathways. Over one third of patients were referred from primary care (50 from General Practice and 1 from dental practitioner). Two thirds were referred from secondary care, the majority of referrals from rheumatology, neurology and oral medicine. Sixty-four patients had a diagnosis of PSS confirmed as per AECG criteria. 88 (58.7%) patients had a labial salivary gland biopsy, and of these 46 were diagnosed with PSS. Time to treatment varied, in fact many patients had commenced treatment (in particular replacement therapy) prior to referral. DMARDs were commenced in 30 patients. Four patients were referred for clinical trial with rituximab/placebo due to the severity of their symptoms. Conclusions: The findings from our analysis conform with the epidemiology in terms of gender bias and age at presentation. There is a significant delay from the onset of symptoms to referral. This may be due to delayed presentation by the patient (most commonly), or delayed referral. It became clear that there are key referrers (in particular ophthalmology, oral medicine and neurology) due to the nature of the disease. It may be suggested that a combined clinic involving these specialties may be both financially beneficial and result in a timely diagnosis. With current research focusing on immunomodulatory therapies to treat symptoms and prevent systemic damage, it is essential that these patients are referred as early as possible and that a baseline assessment of their disease is undertaken in order to monitor progression of disease and prevent irreversible damage. The pro forma developed as part of this audit ensures thorough investigation and documentation of disease markers. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2104